Leadership Influence on Quality Enhancement of Community Colleges - Bhusal, Babu Ram (JMC Research Journal, 2018)
This study was conducted as an attempt to see the influence of educational leadership on employees for motivating them in quality enhancement mission. The assumption behind it was the need of creative and innovative leadership for motivated and efficient team spirit in quality education. The research questions were centralized in the leadership perceptions and their strategic efforts for imparting quality education. The philosophical and theoretical support of transformational leadership theory and continuous improvement approach strengthened the research. The researcher adopted interpretive research paradigm with in- depth interview and field observation as primary sources and various printed documents as the secondary sources. The basic data were generated from twelve participants of three different community colleges. The perceived data were presented and interpreted under various themes via perceptions and efforts in quality enhancement, leadership influence on employees, human resource development and mobilization for institutional strength and shifting threats into opportunities. The findings hint varied and insufficient attempts of leaders for addressing growing needs of these colleges. The concluding remarks further encourage college leaders in general and community college leaders in particular to plan and implement farsighted strategies to cope with the ever widening challenges in academia.